PERANCANGAN PERANGKAT LUNAK GENERATOR GAMBAR DAN MUSIK FRAKTAL DENGAN METODE ITERATED FUNCTION SYSTEM - Wahjono, Tri Djoko; Karim, Syaeful; Riyadi, Bayu (Bina Nusantara University, 2007)
Article presents analysis and analyze a software that utilize Geometry Fractal, especially Iterated FunctionSystem Fractal, as art. Research method that has been used in this research is by library study and by laboratoriumstudy to test the performance of the software. Result of the research has shown that converted music by GeometryFractal has various results, which depend on the parameters used in it and type of Geometry Fractal image produced.It can be said that usage of fractal in high iteration can produce clear image fractal and complicated music fractal.